The Goldilocks contract The synergistic benefits of combining structure and autonomy for persistence, creativity, and cooperation. - Chou, EileenY; Halevy, Nir
Contracts are commonly used to regulate a wide range of interactions and relationships. Yet relying on contracts as a mechanism of control often comes at a cost to motivation. Integrating theoretical perspectives from psychology, economics, and organizational theory, we explore this control-motivation dilemma inherent in contracts and present the Contract-Autonomy-Motivation-Performance-Structure (CAMPS) model, which highlights the synergistic benefits of combining structure and autonomy. The model proposes that subtle reductions in the specificity of a contract's language can boost autonomy, which increases intrinsic motivation and improves a range of desirable behaviors. Nine field and laboratory experiments found that less specific contracts increased task persistence, creativity, and cooperation, both immediately and longitudinally, because they boosted autonomy and intrinsic motivation. These positive effects, however, only occurred when contracts provided sufficient structure. Furthermore, the effects were limited to control-oriented clauses (i.e., legal clauses), and did not extend to coordination-oriented clauses (i.e., technical clauses). That is, there were synergistic benefits when a contract served as a scaffold that combined structure with general clauses. Overall, the current model and experiments identify a low-cost solution to the common problem of regulating social relationships: finding the right amount of contract specificity promotes desirable outcomes, including behaviors that are notoriously difficult to contract. The CAMPS model and the current set of empirical findings explain why, when, and how contracts can be used as an effective motivational tool.